Teacher and administrator perceptions of gender in the classroom. Issue 3 (27th May 2018) - Morrissette, Victoria; Jesme, Shannon; Hunter, Cheryl
Abstract: Gendered stereotypes persist in American classrooms despite efforts to create equitable learning environments. Within this qualitative study, we examined both teachers' and administrators' perceptions of gender in the classroom and present the data of the continued gender bias among some educators in their own words. The data showed teachers and administrators attributed conflict styles based upon gender and consistently reference boys conflict resolution style as "over quickly" in contrast to girls conflict resolution style. Likewise, participants' gendered perceptions extended to the kinds of feedback they expected girls and boys to prefer. Additionally, our findings show that participants misunderstood or lacked knowledge of scientifically sound research and participants described changing the curriculum in a single-sex class/school to use stereotypical topics and activities for student engagement. The authors suggest this data should open a discussion between education scholars and practitioners to help align current knowledge about gender and development and implications of stereotypes for classroom practice.